Message from the Executive Director - Downey, Chris (Operating Room Nurses Association of Canada Journal, 2024)
With summer ’21 waning, our thoughts turn to the fall season and getting back to full steam ahead. With our newest Board Members in place the summer months allowed time for general orientation and refinement of our strategic plan. With our structure defined, our terms of reference outlined, the board now begins implementing its goals and objectives for a one year, three year, and five year timeframe.